Financing Common Goods for Health: A Country Agenda - Susan P. Sparkes; Joseph Kutzin; Alexandra J. Earle (Taylor & Francis Group, 2019)
Collective financing, in the form of either public domestic revenues or pooled donor funding, at the country level is necessary to finance common goods for health, which are population-based functions or interventions that contribute to health and have the characteristics of public goods. Financing of common goods for health is an important part of policy efforts to move towards Universal Health Coverage (UHC). This paper builds from country experiences and budget documents to provide an evidence-based argument about how government and donor financing can be reorganized to enable more efficient delivery of common goods for health. Issues related to fragmentation of financing-within the health sector, across sectors, and across levels of government-emerge as key constraints. Effectively addressing fragmentation issues requires: (i) pooling funding and consolidating governance structures to repackage functions across programs; (ii) aligning budgets with efficient delivery strategies to enable intersectoral approaches and related accountability structures; and (iii) coordinating and incentivizing investments across levels of government. This policy response is both technical in nature and also highly political as it requires realigning budgets and organizational structures.